Young football players' dietary beliefs and practices - a qualitative study - Bjørnvåg, Aleksander (UiT The Arctic University of Norway, 2023)
The purpose of this master's thesis is to investigate the dietary habits and beliefs among young football players and to examine whether there are differences between those participating in private sports programs in Eastern Norway and those participating in public sports programs in Finnmark. Through qualitative interviews with six young football players, the study has found that young athletes heavily rely on advice from coaches and family members when it comes to their diet, and they face significant challenges in trying to maintain healthy eating habits while balancing school and training. The study emphasizes the need for collaboration between schools and sports clubs to provide more comprehensive education and support to young athletes regarding their dietary practices and beliefs. Furthermore, geographic, and resource-related factors should be taken into consideration when developing targeted interventions aimed at improving nutritional knowledge. The valuable insights into the dietary habits and beliefs of young football players have important implications for strengthening the nutritional support provided to young athletes. By utilizing a combination of inductive and deductive data analysis, significant implications related to supporting the nutritional needs of young athletes emerge. These findings have important implications for enhancing the nutritional support offered to young athletes. Masteroppgavens formål er å undersøke kostholdsvanene og troen knyttet til kosthold hos unge fotballspillere, og se om det er noen forskjeller mellom de som deltar i private idrettsprogrammer på Østlandet og de som deltar i offentlige idrettsprogrammer i Finnmark. Kvalitative intervjuer med seks unge fotballspillere viser at unge idrettsutøvere i stor grad er avhengige av råd fra trenere og familiemedlemmer når det gjelder kosthold. De står også overfor betydelige utfordringer når de forsøker å opprettholde sunne spisevaner, samtidig som de balanserer skole og trening. Studien understreker behovet for samarbeid ...